2021
DOI: 10.1016/j.ekir.2020.10.015
|View full text |Cite|
|
Sign up to set email alerts
|

Increased Lifetime Risk of ESRD in Familial IgA Nephropathy

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…Our observation indicates that the prevalence of positive-FH was 11.6% among histologically proven, primary IgAN cases. The incidence of family clustering is almost comparable to that in previous studies: 6.7% in China [ 8 ] and 17.2–34% in Italy [ 5 ] (Additional file 2 ). Other studies with Caucasians showed a lower frequency of familial aggregation in total sporadic cases: 1.8% in Ireland [ 6 ] and 1.4% in the US [ 15 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our observation indicates that the prevalence of positive-FH was 11.6% among histologically proven, primary IgAN cases. The incidence of family clustering is almost comparable to that in previous studies: 6.7% in China [ 8 ] and 17.2–34% in Italy [ 5 ] (Additional file 2 ). Other studies with Caucasians showed a lower frequency of familial aggregation in total sporadic cases: 1.8% in Ireland [ 6 ] and 1.4% in the US [ 15 ].…”
Section: Discussionsupporting
confidence: 81%
“…A majority of IgAN cases are sporadic, while some show a familial cluster of renal diseases. Familial aggregation of IgAN is observed among IgAN patients of various ethnic backgrounds [ 1 , 3 8 ], suggesting the existence of a genetic component to the disease worldwide. In most cases, the clustering pattern is autosomal dominant with variable penetrance; however, some pedigrees may fit with a more complex genetic mode [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a recent study suggested that familial forms of IgA nephropathy are associated with increased lifetime risk of kidney failure. 12 Future studies will need to assess whether a positive family history of CKD also predicts complications of CKD such as progression or risk of cardiovascular disease. Moreover, it would be interesting to determine whether the risk imparted varies across different CKD categories such as glomerular diseases or diabetic nephropathy.…”
mentioning
confidence: 99%